Mechanistic insights into the chemical structural changes of lignite on potential formation of the polycyclic aromatic hydrocarbons. (November 2022) - Dong, Tao; Hao, Zhifei; Zhang, Yinmin; Zhang, Yongfeng
Abstract: Polycyclic aromatic hydrocarbons (PAHs) generated during lignite combustion and gasification are highly carcinogenic, teratogenic, and mutagenic. Leveraging solvent extraction without damaging the macromolecular structure of lignite could help better understand the chemical structure and further clarify the possible source of PAHs, and the possibility of their elimination, thereby improving lignite utilization efficiency. In this study, methanol, ethanol, dichloromethane, and n-hexane were used to extract the feedstock at room temperature, and the constituents of the extracts were analyzed using GC-MS. The study showed that poly-condensed aromatic constituents were present in relatively high percentage in the extracts, due to the polarity effect of solvents, and could have a noticeable impact on the generation of PAHs. The aromatic hydrocarbons content accounts for nearly 70% of the total, which is about 10% higher than that of aliphatic hydrocarbons, and mainly exist in the form of 2 and 3 rings. Furthermore, FTIR, XRD and Raman were used to evaluate the macromolecular structural characteristics and the relevant information of the lignite bonds. The study demonstrated that the rupture of weak C–O or C–C covalent bonds promoted a more aromatic product, as strongly cross-linked networks of polycyclic aromatic components remained. The potential generation of PAHs was comprehensively ascertained by evaluating the extracts obtained at room temperature and products of combustion test， which can provide more information on PAHs pollutants. Graphical abstract: Image 1 Highlights: The effect of structure of lignite on generation of PAHs was investigated. Relatively high percentage of aromatic hydrocarbons were present in extracts. Generation of condensed aromatic components was caused by polarity of solvents. Aromatic compounds of 2–4 rings was seen as precursors on generation of PAHs.